The increase of VEGF expressions and new blood vessels formation in Wistar rats induced with post-tooth extraction sponge amnion - Moh. Basroni Rizal; Elly Munadziroh; Indah Listiana Kriswandini (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Tooth extraction is the process of removing a tooth from the oral cavity potentially triggering a wound healing response in the body. As a result, many methods have been applied to improve the wound healing process, especially in wounds resulting in complications. One such method involves the application of amniotic membrane which has anti-inflammatory, anti-bacterial, anti-fibrosis, anti-scarring properties with low immunogenicity, epithelialization effects, and secretory leukocyte protease inhibitor (SLPI). It also contains collagen, various growth factors, transferrin, fibronectin, nidogen, proteoglycans, hyaluronan, and laminin. Purpose: This study aimed to determine the effects of sponge amnion on the number of VEGF expressions and new blood vessels in post-tooth extraction wounds of Wistar rats. Methods: Sponge amnion was produced by mixing freeze-dried amnion membrane from the Tissue Bank at RSUD Dr. Soetomo with 1% gelatin before freeze drying the mixture. Wistar rats were then divided into two groups. In Group 1, referred to as the control group, the post-extraction wounds of the rats received no treatment. Meanwhile, in Group 2, the treatment group, the subjects’ post-extraction wounds were treated with sponge amnion. The rats of both groups were sacrificed on day 3 to allow observation of the number of VEGF expressions and new blood vessels. A statistical analysis test, a t-test, was subsequently conducted. Results: There was a significant difference in the number of new blood vessels in the control group and that of the treatment group with a p value of 0.018 (p<0.05). There was also a significant difference in VEGF expression between the two groups with a p value of 0.000 (p <0.05). Conclusion: Sponge amnion can generate a number of VEGF expressions and new blood vessels in the post-extraction wounds of Wistar rats.